Mathmarvel 1.0 / Nadiah Mohamed ... [et al.]. - Mohamed, Nadiah; Yaacob, Nurul Aityqah; Mahayadin, Mahfuzah; Othman, Norlida; Mohd Ruslan, Siti Zaharah; Andu, Yusrina; Ismail, Norul Fadhilah; Jaafar, Nor Fadhlin; Ahmad, Mardiana (Universiti Teknologi MARA, Negeri Sembilan, 2024)
From November 24, 2023, to January 5, 2024, MathMarvel 1.0 was hosted by the College of Computing, Informatics, and Mathematics Studies at UiTM Cawangan Negeri Sembilan, Kampus Kuala Pilah. This program had a specific goal: to provide support and assistance to a cohort of 150 students. The participants included those enrolled in pre-science and diploma programs, specifically under codes MAT037, MAT013, MAT083, MAT112, and MAT133. The selection criteria for participation were rooted in the initial poor performance of students in their first assessments. The intent was to intervene proactively and address areas of struggle to mitigate the risk of potential failure in the final exams. This approach aimed to create a conducive learning environment and facilitate a positive academic outcome for the participating students.